Influenza surveillance - Pereira, M. (1978)
The main objectives of influenza surveillance are: to measure the impact of the disease by collection and analysis of epidemiological information on morbidity and mortality, and to anticipate future epidemics and pandemics by the collection and analysis of influenza viruses. The World Health Organization's influenza programme is based on the collaboration of 98 national influenza centres in 70 countries and the 2 WHO Collaborating Centres in Atlanta and London. Epidemiological information may be based on morbidity figures derived from a variety of sources such as returns from physicians or hospitals; mortality statistics or new claims for sickness benefit; school or industrial absenteeism, etc. The laboratory aspects of influenza epidemiology are certainly more uniformly covered than the statistical aspects. Since the advent of the A/Hong Kong/1/68 (H3N2) influenza virus A subtype there have been a number of variants with antigenic ”drift” but only three succeeded in causing widespread epidemics: A/England/42/72, A/Port Chalmers/1/73, and A/Victoria/3/75. In 1972, the influenza B virus also showed some antigenic ”drift”, the new variants being characterized by B/Hong Kong/5/72. Whenever a new variant appears, the degree of protection afforded to the population by the available vaccine is assessed. In the light of these data, WHO publishes annually in the Weekly epidemiological record recommendations formulated by the WHO Collaborating Centres on vaccine composition.